Parameter estimation for fractional-order nonlinear systems based on improved sparrow search algorithm - Zhou, Yongqiang; Yang, Renhuan; Chen, Yibin; Huang, Qidong; Shen, Chao; Yang, Xiuzeng; Zhang, Ling; Wei, Mengyu (International journal of modern physics. C, Computational physics, physical computation, 2024)
Parameter estimation is important in the study of control and synchronization of fractional-order nonlinear systems (FONSs). This paper proposes an improved Sparrow Search Algorithm (ISSA) for the parameter estimation problem of FONSs. The algorithm improves the population initialization, position update method of discoverers and warning sparrows based on Sparrow Search Algorithm (SSA), and the parameter estimation simulation experiment for fractional-order financial nonlinear system and fractional-order L nonlinear system is conducted to demonstrate this method. The experimental results show that the proposed ISSA is superior to the SSA, Particle Swarm Optimization (PSO), Whale Optimization Algorithm (WOA) and Harris Hawks Optimization (HHO) in terms of parameter optimization accuracy and convergence speed, which validates the advantages of the ISSA.